Circularity in Knitting: The Potential of Re-Using Natural Yarns After Unraveling - Nadiia P. Bukhonka; Olena Kyzymchuk (Journal of Natural Fibers)
Currently, there is an increasing focus on sustainable textile manufacturing in terms of reducing the waste generated during the production and pre-consumer stages. Knitting companies are exploring the promising direction of unraveling and upcycling yarn to achieve this goal. To assess the knittability of unraveled yarn vis-a-vis conventional yarn, a comprehensive indicator of yarn-breaking force changes was proposed. The purpose of this study is to present a method to evaluate the strength property of unraveled yarn and to investigate the potential of 74-tex cotton and 72-tex wool yarn for future upcycling in knitting. The results of the investigation revealed that cotton yarn has a higher potential for upcycling both at pre- and post-consumer stages, compared to wool yarn. The knittability of unraveled cotton yarn is almost 99% after knitting and dry relaxation and over 95% after repeated washing and drying cycles. However, it is pertinent to note that repeated ironing impacts the cotton yarn’s knittability, and hence, it is recommended to label future upcycling products with a special marking prohibiting ironing. The possibility of unraveling and reusing wool yarn is limited to the post-production and pre-consumer stages when its knittability is near 95%.